Phân tích đa thức sau thành nhân tử:
x^2+7xy+9x+12y^2+7y+6
phân tích đa thức sau thành nhân tử:x^2-y^2+7x-7y
(x^2 +7x)-(y^2+7y)
=x(x+7)-y(y+7)
=(x+7)(y+7)(x-y)
Phân tích đa thức thành nhân tử
X^2+7xy+9x+12y^2+7y+6
Thanks
phân tích đa thức sau thành nhân tử:x^6-3x^4+3x^2-1-y^3
12y - 9x^2 + 36 - 3x^2y (Phân tích đa thức thành nhân tử)
\(12y-9x^2+36-3x^2y\)
\(=\left(36-9x^2\right)-\left(3x^2y-12y\right)\)
\(=-9\left(x^2-4\right)-3y\left(x^2-4\right)\)
\(=\left(-3\right)\left(x-2\right)\left(x+2\right)\left(3+y\right)\)
\(12y-9x^2+36-3x^2y\)
\(=\left(12y-3x^2y\right)-\left(9x^2-36\right)\)
\(=3y\left(4-x^2\right)-9\left(x^2-4\right)\)
\(=3y\left(4-x^2\right)+9\left(4-x^2\right)\)
\(=\left(3y+9\right)\left(4-x^2\right)\)
\(=3\left(y+3\right)\left[\left(2^2\right)-x^2\right]\)
\(=3\left(y+3\right)\left(2+x\right)\left(2-x\right)\)
Phân tích đa thức thành nhân tử:x^2+x+6
\(=x^2+2x\cdot\frac{1}{2}+\frac{1}{4}-\left(\frac{\sqrt{23}}{2}i\right)^2\)
\(=\left(x+\frac{1}{2}\right)^2\)\(-\left(\frac{\sqrt{23}}{2}i\right)^2\)
\(\left(x+\frac{1}{2}-\frac{\sqrt{23}}{2}i\right)\left(x+\frac{1}{2}+\frac{\sqrt[]{23}}{2}i\right)\)
phân tích đa thức sau thành nhân tử:
x^2+7x+12
\(x^2+7x+12=x\left(x+3\right)+4\left(x+3\right)=\left(x+3\right)\left(x+4\right)\)
\(=x^2+3x+4x+12\)
\(=x\left(x+3\right)+4\left(x+3\right)\)
\(=\left(x+3\right)\left(x+4\right)\)
Phân tích đa thức sau thành nhân tử:
x^2/4+2xy+4y^2
\(\dfrac{1}{4}x^2+2xy+4y^2=\left(\dfrac{1}{2}x+2y\right)^2\)
Phân tích đa thức thành nhân tử
a)3x^2-12xy-4x+8y+7y^2+1
b)12x^2+5x-12y^2+12y-10xy-3
phân tích đa thức sau thành nhân tử:x^4-5x^2y^2+4y^4
\(x^4-5x^2y^2+4y^4\)
\(=\left(x^2\right)^2-2x^22y^2+\left(2y^2\right)^2-x^2y^2\)
\(=\left(x^2-2y^2\right)^2-\left(xy\right)^2\)
\(=\left(x^2-2y^2-xy\right)\left(x^2-2y^2+xy\right)\)